Retirement Illusion And Reality Compared: Reports Of Prospective Retirees And Retired Teachers In Nigeria - Olatomide, Onijuni Olufemi (Academic Journal of Psychology and Counseling, 2025)
Prospective retirees usually prepare for what they thought they would need for retirement adjustment while retired ones are better positioned to evaluate the adequacy of their earlier preparedness, judged by retirement reality. This survey investigated the pre-retirement guidance needs of retirement-eligible teachers, explored retroactive retirement guidance needs of retired teachers, and compared the results of the two groups. A sample (n=305; 151 prospective teacher-retirees; 154 retired teachers) was selected, while three research questions guided the study. Results showed the 16 items in the pre-retirement guidance needs are potential needs for teachers entering retirement (Item’s RSI>0.05), and the 16 items in the retrospective retirement guidance needs are areas that retired teachers opined they missed while preparing for retirement (Item’s RSI>0.05). Prospective retirees and retired teachers also ranked guidance needs in different orders, but they tallied two items of needs. The findings underpin the necessity for periodically administering retirement preparedness and retirement readiness instruments to workers to provide person-fit retirement counseling as they advance toward retirement.